2003
DOI: 10.1248/cpb.51.1448
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of 3-O-Acyl-(+)-catechins on Epstein-Barr Virus Activation

Abstract: As an exploratory investigation of antitumor-promoting catechins, we tried to synthesize the (Ϫ)-epigallocatechins (EGCs) possessing an acyl group.1,2) An acyl group was introduced at the C-3 hydroxy group of (Ϫ)-EGC (2), which is less responsible for radical-scavenging action than the phenolic hydroxyl groups, 3,4) to improve their pharmacokinetic profile such as cell membrane and tissue permeability. The EGCs with the C-3 acyl chain of C 8 -C 11 carbon atoms showed marked antitumor-promoting activities both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Octanoic acid and oxacillin were purchased from Sigma (Poole, UK). The acyl-(+)-catechin derivatives and 3-O-octanoyl-(−)-epicatechin were synthesised in the Department of Biotechnology, Kansai University, Osaka, Japan as previously described [12]. Structures of the catechins used in this study are shown in Table 1.…”
Section: Reagents and Bacterial Strainsmentioning
confidence: 99%
“…Octanoic acid and oxacillin were purchased from Sigma (Poole, UK). The acyl-(+)-catechin derivatives and 3-O-octanoyl-(−)-epicatechin were synthesised in the Department of Biotechnology, Kansai University, Osaka, Japan as previously described [12]. Structures of the catechins used in this study are shown in Table 1.…”
Section: Reagents and Bacterial Strainsmentioning
confidence: 99%
“…6-Hydroxy-2,5,7,8-tetramethyl-chroman-2-carboxylic acid (Trolox) was a product of Sigma-Aldrich, Milwaukee, U.S.A. 3-O-Octanoyl-(+)-catechin was synthesized and purified as described in a previous report. 6) Other chemicals were of reagent grade. ABTS Radical Cation Decolorization Assay ---The radical scavenging activity of antioxidants for ABTS radical cations was measured according to the methods of Re et al 7) A stock solution of ABTS radical cations was prepared one day before the assay by mixing 5 ml of 7 mM ABTS with 1 ml of 14.7 mM potassium persulfate, followed by storage *To whom correspondence should be addressed: Department of Food and Nutrition, Kyoto Women's University, 35 Kitahiyoshicho, Imakumano, Higashiyama-ku, Kyoto 605-8501, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…4) It has been reported that several newly synthesized 3-O-acyl-(+)-catechins, as well as 3-O-acyl-(-)-epigallocatechins, inhibited the activation of the Epstein-Barr virus early antigen more strongly than catechins lacking the 3-O-acyl group. 5,6) 3-OOctanoyl-(+)-catechin was one of the most effective derivatives. The evidence suggests that modification of 3-OH group of catechins could enhance the biological functions of the original catechins.…”
Section: Introductionmentioning
confidence: 99%
“…Fragrant compounds should increase the sterilizing activity of liquors. Teas, especially green tea, have anti-microbial and anti-viral activities, but it is likely that these effects come from catechin derivatives such as epigallochatechin 3-O-gallate (Uesato et al, 2003).…”
Section: Anti-bacterial Activitymentioning
confidence: 99%